The Role of The Linguistic Environment for Developing Speaking Skills: A Case Study at The Hidayatullah Batu Institute Based on The Behavioral Theory of Albert Bandura - Azis, Abdul Jalil; Bakhiet, Bakri Muhammad; Chamidah, Dewi (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
This study investigates the role of the language environment in developing speaking skills among students at Hidayatullah Batu Institute, using Albert Bandura’s behavioral theory as a framework. The research was conducted to explore how creating a supportive and motivating Arabic language environment in a non-Arabic speaking context like Indonesia can enhance students’ oral language proficiency through modeling, positive reinforcement, and social interaction. A qualitative case study methodology was applied. Data were collected via direct observations, structured interviews with twelve key informants including the institute’s director, teachers, and students, as well as institutional documents. Data were collected over a four-week period through repeated observation and semi-structured interviews, The analysis followed Miles and Huberman’s model, involving data reduction, data display, and drawing conclusions. Triangulation was used to increase the credibility of the findings. Results show that the institute effectively establishes an immersive Arabic language environment that encourages daily language use both inside and outside the classroom. Students improve their speaking skills by observing and imitating proficient language models such as teachers and peers. Positive reinforcement through praise and symbolic rewards motivates students to participate actively. Planned linguistic activities like daily conversations, educational drama, and language games help reduce speaking anxiety and build fluency. The study also found significant progress in pronunciation, sentence construction, and a reduction of interference from students’ native languages. These combined behavioral approaches and diverse activities create a natural, confident, and sustainable improvement in students’ speaking abilities.